An investigation of calcium carbonate core-shell particles for incorporation of 225Ac and sequester of daughter radionuclides: in vitro and in vivo studies; Journal of Controlled Release; Vol. 330 - Muslimov A. R. Albert Radikovich; Antuganov D. Dmitrii; Tarakanchikova Ya. V. Yana Vladimirovna; Karpov T. E. Timofey Evgenjevich; Zhukov M. V. Mikhail Vladimirovich; Zyuzin M. V. Mikhail; Timin A. S. Aleksandr Sergeevich (2021, 2021)
Title screen